Numerical and experimental investigation on the hybrid superplastic forming of the conical Mg alloy component - Guo, Mei Ling (2020)
Hybrid superplastic forming (SPF) is a novel sheet metal forming technique that combines hot drawing with gas forming process. Compared with the conventional SPF process, the thickness distribution of AZ31 part formed by this hybrid SPF method has been significantly improved. Additionally, the microstructure evolution of AZ31 was examined by electron backscatter diffraction (EBSD). Many subgrains with low misorientation angle were observed in the coarse grains during SPF. Based on the tensile test results, parameters of hyperbolic sine creep law model was determined at 400 ºC. The hybrid SPF behavior of non-superplastic grade AZ31 was predicted by ABAQUS using this material forming model. The FEM results of thickness distribution, thinning characteristics and forming height were compared with the experimental results and have shown reasonable agreement with each other.